2019
DOI: 10.1038/s41419-019-2081-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct impact of cisplatin on mitochondria induces ROS production that dictates cell fate of ovarian cancer cells

Abstract: Patients with high-grade serous ovarian cancer (HGSC) frequently receive platinum-based chemotherapeutics, such as cisplatin. Cisplatin binds to DNA and induces DNA-damage culminating in mitochondria-mediated apoptosis. Interestingly, mitochondrial DNA is critically affected by cisplatin but its relevance in cell death induction is scarcely investigated. We find that cisplatin sensitive HGSC cell lines contain higher mitochondrial content and higher levels of mitochondrial ROS (mtROS) than cells resistant to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
207
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(251 citation statements)
references
References 40 publications
(55 reference statements)
12
207
0
Order By: Relevance
“…8A). This suggests that the cisplatin is not lowering the mitochondrial membrane potential, which agrees with Kleih and colleagues who observed that ovarian cancer cells treated with cisplatin also maintained their mitochondrial membrane potential (Cocetta et al 2019;Kleih et al 2019). Similarly, English et.…”
Section: Cisplatin Treatment Induced Apoptosis Without Significantly supporting
confidence: 84%
“…8A). This suggests that the cisplatin is not lowering the mitochondrial membrane potential, which agrees with Kleih and colleagues who observed that ovarian cancer cells treated with cisplatin also maintained their mitochondrial membrane potential (Cocetta et al 2019;Kleih et al 2019). Similarly, English et.…”
Section: Cisplatin Treatment Induced Apoptosis Without Significantly supporting
confidence: 84%
“…The co-administration of MDR1 inhibitors with PARPi is a strategy that has not yet been explored in clinical trials [75], but future research may focus on targeting patients with ABCB1 mutations involved in PARPi resistance. Alteration in intracellular proteins that are able to bind and sequester platinum (including metallothioneins and glutathione [76,77]), and altered expression of pro-survival or anti-survival proteins have also been described as resistance mechanisms which reduce cellular availability of drugs. Proteomic analysis of paired primary and recurrent OC cells from ascites has revealed that RELA and STAT5 proteins cooperate in inducing the anti-apoptotic Bcl-X promoter activity and synergistically enhance Bcl-xL expression in chemo-resistant ovarian cancer cells [78].…”
Section: Reduced Cellular Availability Of Drugsmentioning
confidence: 99%
“…ROS is an active form of oxygen, and its induced cytotoxicity is an important mechanism for cisplatin to kill tumor cells [13]. Cisplatin induces high ROS levels that cause cancer cell apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%